The Roles of Motivation to Learn and Coping Behaviours in Managing Stress in Working College Students - Cempaka Putrie Dimala; Ratih Saraswati (Journal of Educational Science and Technology (EST), 2023)
This study aims to determine the effectiveness of positive self-talk to increase the self-confidence of psychology students at Buana Perjuangan University, Karawang. This study uses a one group pre-test post-test design. The population in this study were psychology students from the 2018 class. The sampling technique used was purposive sampling and the sample consisted of 11 students. The instrument used in this study is a self-confidence scale that has been tested starting from expert judgment to reliability testing. The reliability of the confidence scale that was tested using Cronbach Alpha obtained a coefficient of 0.896 which indicates a very good level of reliability. Hypothesis testing using paired samples test assisted through SPSS version 23 for windows program. The results showed that the treatment with positive self-talk techniques was effective in increasing the self-confidence of psychology students. This can be seen in the paired samples test, the results of the pre-test and post-test scores of the experimental group obtained a Sig (2-tailed) value of 0.005 < 0.05, which means H0 is rejected and Ha is accepted.